Failure mechanisms in metal–metal nanolaminates at elevated temperatures: Microcompression of Cu–W multilayers. (15th March 2015) - Wheeler, J.M.; Raghavan, R.; Chawla, V.; Zechner, J.; Utke, I.; Michler, J.
Abstract : Nanolaminates of Cu and W with a bilayer thickness ratio of 1:1 and individual layer thicknesses of 5, 20 and 100 nm were studied by using elevated temperature microcompression. Failure in all the multilayers with different interlayer thicknesses occurs by rupture of the W interlayers, resulting in local strain softening and shearing at ambient temperature and lateral plastic flow of the Cu layers confined between the harder W layers at lower stresses with increasing testing temperatures.